In situ reactive extraction with oleic acid for process intensification in amine transaminase catalyzed reactions. Issue 1 (10th December 2021) - Doeker, Moritz; Grabowski, Laura; Rother, Dörte; Jupke, Andreas
Abstract : Efficiency of the enzymatic metaraminol production with the amine donor l -alanine was increased by applying reactive extraction as suitable in situ product removal strategy. Abstract : Amine transaminase catalyzed reaction systems allow the efficient production of high value active pharmaceutical ingredients via stereoselective amination of prochiral precursors. Metaraminol is a bioactive amino alcohol directly used in hypotension treatment and further acts as important precursor for the synthesis of more complex bioactive compounds. The amination reaction to such compounds makes use of an amine donor, which is usually derived from non-renewable resources despite other drawbacks. To allow a greener production route to metaraminol, l -alanine can be used as an alternative amine donor, although conversions are thermodynamically limited. To overcome this limitation, extraction-based in situ product removal (ISPR) can be applied to achieve higher conversions. Here, we describe a reactive extraction strategy to recover metaraminol under transaminase-favorable process conditions, achieving higher yields as for previously described physical extraction concepts. Suitable process parameters, such as pH and required reactant concentration were defined by extraction experiments and enzyme compatibility tests. An operational window was found to establish reactive ISPR within the biocatalytic production of metaraminol. Our approach makes use of oleic acid as a sustainable reactant and allows efficient in situ recovery of metaraminol, thus improving the enzymatic production.